How to kill a guy in ten dates : a novel - Thompson, Shailee (Gallery Books, 2026)
"A humorous, swoony, and downright terrifying slasher rom-com in which a cinephile gets caught in the middle of a murder spree at a speed-dating event and must use her encyclopedic knowledge of the romance and horror genres to make it as a real-life Final Girl. When Jamie Prescott and her best friend Laurie attend a speed-dating event,Jamie expects to meet a roster of mediocre men and indulge in some street food afterwards. She doesn't expect one of her dates to have his throat slit at their table during a blackout. After the lights come back on and there are more bodies on the floor, it becomes clearthat dating can be a very dangerous pastime. Armed with makeshift weapons and Jamie's extensive knowledge of what NOT to do in a slasher, the remaining speed daters try to find an exit while the killer adds to their body count. As the night progresses and Jamie comes face-to-mask with the murderer, she begins to suspect they are committing the slayings to woo one of the daters and turn them into a real-life Final Girl. But Jamie has other plans, and as she fights for herlife, she can't help but find herself ensconced in a love triangle with two of the other survivors. Will she make it through the bloodshed to find her Happily Ever After? Or does this machete-wielding psychopath have another ending in mind?"--